Size and diet of Oreochromis niloticus in an urban drainage channel in Santos, State of São Paulo, Brazil - Costa, João Henrique Alliprandini da; Miranda, Rebeca Ribeiro; De-Carli, Bruno Paes; Selinger, Amanda; Ribeiro, Renan Braga; Souza, Ursulla Pereira (Acta Scientiarum. Biological Sciences, 2025)
The introduction of non-native species can significantly impact ecosystems, with the Nile tilapia (Oreochromis niloticus) serving as a notable example. Despite its widespread presence in various rivers and reservoirs, its occurrence, particularly its dietary habits in drainage channels, remains insufficiently explored. Therefore, the present study investigated the ecological dynamics of O. niloticus within an urban drainage channel system in Santos, São Paulo, Brazil. Sampling of 56 individuals across four campaigns revealed a dynamic population structure, characterized by seasonal variation in size, notably the prevalence of mature females during periods of increased rainfall. The sex ratio did not deviate significantly from the expected ratio (1:1). Analyses of size and weight demonstrated significant fluctuations across sampling months, suggesting potential variations in reproductive activities and population dynamics. The condition factor remained remarkably consistent, indicating stable health conditions despite intra-annual variations. Dietary analysis indicated a distinct preference for detritus, consistent with the species’ characteristic foraging behavior on the channel bed. The correlations between water turbidity, stomach food item richness, and preference for detritus suggest that, in murkier waters, foraging on sediment-rich organic matter becomes more productive. Regarding shifts in diet composition, this species exhibited opportunistic feeding habits throughout all seasons, highlighting its adaptability to urban environments.